Wireless mesh networks - Held, Gilbert, 1943- (Auerbach Publications, 2005)
"Wireless mesh networking is a new technology that has the potential to revolutionize how we access the Internet and communicate with co-workers and friends. Wireless Mesh Networks examines the concept and explores its advantages over existing technologies. This book explores existing and future applications, and examines how some of the networking protocols operate."